Assessing the impact of the memoranda on Greek labour market and labour relations - Dedoussopoulos, Apostolos (Geneva, 2013)
"This paper is part of a series of studies funded by the European Commission in the framework of a project of the International Labour Organization (ILO) on “Promoting a balanced and inclusive recovery from the crisis in Europe through sound industrial relations and social dialogue”. The project falls under a recent partnership agreement between the ILO and the European Commission, which aims to study the impact of the crisis and crisis-response policies on national tripartite social dialogue, collective bargaining and labour law in the Member States of the ILO and the European Union (EU), and the role of social dialogue actors and institutions in this context."